Controlling axonal regeneration with acellular nerve allograft limits neuroma formation in peripheral nerve transection: An experimental study in a swine model. Issue 6 (4th August 2022) - Grimm, Patrick D.; Wheatley, Benjamin M.; Tomasino, Allison; Leonhardt, Crystal; Hunter, Daniel A.; Wood, Matthew D.; Moore, Amy M.; Davis, Thomas A.; Tintle, Scott M.
Abstract: Background: Symptomatic neuromata are a common indication for revision surgery following amputation. Previously described treatments, including traction neurectomy, nerve transposition, targeted muscle re‐innervation, and nerve capping, have provided inconsistent results or are technically challenging. Prior research using acellular nerve allografts (ANA) has shown controlled termination of axonal regrowth in long grafts. The purpose of this study was to determine the ability of a long ANA to prevent neuroma formation following transection of a peripheral nerve in a swine model. Materials and Methods: Twenty‐two adult female Yucatan miniature swine ( Sus scrofa ; 4–6 months, 15–25 kg) were assigned to control (ulnar nerve transection only, n  = 10), treatment (ulnar transection and coaptation of 50 mm ANA, n  = 10), or donor ( n  = 2) groups. Nerves harvested from donor group animals were treated to create the ANA. After 20 weeks, the transected nerves including any neuroma or graft were harvested. Both qualitative (nerve architecture, axonal sprouting) and quantitative histologic analyses (myelinated axon number, cross sectional area of nerve tissue) were performed. Results: Qualitative histologic analysis of control specimens revealed robust axon growth into dense scar tissue. In contrast, the treatment group revealed dwindling axons in the terminal tissue, consistent with attenuated neuroma formation. Quantitative analysis revealed a significantly decreased number of myelinated axons in the treatment group (1232 ± 540) compared to the control group (44, 380 ± 7204) ( p  < .0001). Cross sectional area of nerve tissue was significantly smaller in treatment group (2.83 ± 1.53 mm 2 ) compared to the control group (9.14 ± 1.19 mm 2 ) ( p  = .0012). Conclusions: Aberrant axonal growth is controlled to termination with coaptation of a 50 mm ANA in a swine model of nerve injury. These early results suggest further investigation of this technique to prevent and/or treat neuroma formation.